PENGEMBANGAN DESAIN, KUALITAS PRODUK DAN PEMASARAN BERBASIS DIGITALISASI DALAM MENINGKATKAN DAYA SAING PRODUK USAHA TENUN PADA MIYHA SONGKET KABUPATEN SIJUNJUNG - Triani, Laura Amelia; Lita, Ratni Prima; Komalasari, Sanda i Patrisia; Yanti, Yanti; Rahim, Rida; Suziana, Suziana; Syafira, Tama Aulia; Sari, Dellani Mutia; Fanessa, Fanessa (LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) Universitas Andalas, 2024)
Miyha Songket's business is one of the business groups that produces Unggan weaving. However, this business is not yet optimal in design, product quality and social media marketing. The aim of this activity is to design motifs to be attractive in the eyes of consumers, design motifs digitally so that production is fast, improve product quality and optimize social media marketing to reach the target market. Activity methods are training, practice, discussion and business consultation methods. The training activities were carried out in 2 days consist of motif training and digital motif training. For consultation method carried in 6 months with 6 times consultations in order to make sure about social media development and evaluation of motif created by the craftsmen. There are three stages, namely the preparation, implementation and monitoring activity. The results of the training activities, there was an increase in ability to design motifs and the implementation of digital use in designing motifs. One of them is the presence of 2 craftsmen who are responsible for motif designs such as color combinations, contemporary designs and digital designs. Improving product quality is carried out by providing direction and business consultations to leaders and craftsmen. This is supported by the preparation of product SOPs to maintain products in accordance with specified quality standards. Other strengthening is also carried out through increased marketing through content creation on social media.